We're ready, the system's not – youth perspectives on agricultural careers in South Africa. Issue 2 (3rd April 2019) - Metelerkamp, Luke; Drimie, Scott; Biggs, Reinette
ABSTRACT: In light of rising levels of youth unemployment in South Africa, now at 50 per cent, research was undertaken to better understand the paradox of young people turning away from agricultural employment in spite of such high levels of unemployment in the country. The research brings to light new evidence of youth perspectives on contemporary attitudes, experiences and expectations of work in the agricultural sector in South Africa. The research took a narrative-based approach using SenseMaker as a tool for blended qualitative and quantitative data collection. A sample of 573 youth narratives was drawn from across three sites in the KwaZulu-Natal, Limpopo and Western Cape provinces of South Africa. Findings show that attitudes towards careers in agriculture vary greatly. While a set of negative perceptions emerged from the narratives as anticipated, approximately one third of the respondents expressed a clear interest in and passion for agriculture. This interest persisted in spite of a range of pervasive social norms and stigmas. However, these positive aspirations tended to be at odds with the kinds of jobs created by an increasingly corporatised food regime. The research addresses two key policy documents: The National Development Plan and the National Youth Policy, contributing toward the growing body of literature seeking to understand how agricultural policy based on principles of "accumulation from below" may be formulated. It also provides an empirical evidence base for activists, educators and policy-makers interested in the role of the agricultural sector in addressing youth unemployment in South Africa and elsewhere in Africa.